(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The objective of the research was to know species composition and structure of ex-burned heath forest. Field research was carried out from 23 June to 5 July and 10 to 25 September 2004 on the foot-slope of Semujan Hill, Danau Sentarum National Park, West Kalimantan. Ten-sample units (SU) with each size 10 x 10 m are placed based on random sampling method. On each SU, trees with diameter ï‚³ 2 cm cm were identified and the diameter (DBH) and height are recorded. Fourteen tree species were found within a 0.1 ha SU, consisting of 12 genus and 8 families. Tree density is exponentially decreased from trees with small diameter to trees with big diameter. Key words: species composition, forest structure, ex-burned heath forest, Danau Sentarum National Park, West Kalimantan.